Enhanced piezoelectric and ferroelectric properties of BiFeO3-BaTiO3 lead-free ceramics by optimizing the sintering temperature and dwell time. Issue 10 (August 2018) - Zhu, Li-Feng; Zhang, Bo-Ping; Duan, Jia-Qi; Xun, Bo-Wei; Wang, Ning; Tang, Yu-Cheng; Zhao, Gao-Lei
Abstract: 0.7BiFeO3 -0.3BaTiO3 (BFO-0.3BT) ceramics were prepared to uncover the impacts of sintering temperature ( T S ) and dwell time ( t d ) on the microstructure and electrical properties. With increasing the T S or t d, the grain sizes increase along with the porosity decreases, which is in favor of the alignment of dipole. However, excess T S or t d are inclined to cause the volatilization of Bi2 O3, which deteriorates piezoelectric properties. Because of the R - T two-phase coexistence, low defect ions concentration and porosity, as well as appropriate grain size, the excellent d 33 = 208 pC/N and k p = 35.46% as well as P r = 28.52 μC/cm 2 were achieved in BFO-0.3BT ceramics at T S = 1000 °C and t d = 6 h. In addition, large unipolar strain 0.13% and d 33 * = 256.2 pm/V also were obtained in BFO-0.3BT ceramics at T S = 1000 °C and t d = 6 h. This research indicates that the porosity and defect ion concentration as well as grain size also play an important role in piezoelectric properties in BFO-BT ceramics.